CONFLICT OF INTEREST OFFENCE - Andrei – Lucian PUȘCAȘU (Challenges of the Knowledge Society)
The following study aims to analyze the conflict ot interest provisions offence stipulated under Article 301 of the special part of the new Criminal Code. This adjustment aims criminal liability of public officials who, in the exercise of his duty, acquires an unjust material benefit for himself or for some people with whom he shares certain interests. Through this study we want to set a clear limit between this offence and the other service offences, as well as to highlight the need for such legislation.